Acute masseter dystonia in a pediatric patient receiving aripiprazole and methylphenidate following induction of general anesthesia. Issue 8 (17th April 2017) - LeRiger, Michelle; Williams, Jasper; Duncan‐Wiebe, Greta; Shukry, Mohanad
Summary: An 11‐year‐old male receiving aripiprazole, methylphenidate, and clonidine developed acute masseter dystonia inhibiting tracheal intubation after induction of general anesthesia with propofol and rocuronium. Following emergence, he had trismus and jaw discomfort. Psychiatry consultation suspected an acute dystonic reaction, so diphenhydramine was administered intravenously which resolved symptoms. We suspect chronic aripiprazole and methylphenidate usage combined with propofol administration in the short‐term absence of methylphenidate made this patient susceptible to dystonic reactions.